Midwives’ clinical decision-making in the management of postpartum hemorrhage: A phenomenological study - Rafhani Rosyidah; Nurul Azizah; Evi Rinata (Alma Ata University Press, 2026)
Background: Postpartum hemorrhage (PPH) remains one of the leading causes of maternal mortality worldwide. The management of PPH requires rapid and accurate clinical decision-making by healthcare professionals, particularly midwives who serve as frontline providers in maternal care. In addition to clinical competence, emotional responses, teamwork, and personal values may influence midwives’ decision-making processes during obstetric emergencies. Objectives: This study aimed to explore midwives’ experiences of clinical decision-making in managing postpartum hemorrhage, with consideration of the role of spirituality in clinical practice. Methods: This qualitative phenomenological study involved 14 midwives working in delivery or postpartum units who had direct experience managing at least two PPH cases within the previous year. Participants were selected using purposive sampling until data saturation was achieved at the 14th interview. Data were collected through in-depth semi-structured interviews and field notes and analyzed using the Colaizzi phenomenological method. Trustworthiness was strengthened through member checking, source triangulation across participants and hospital contexts, peer debriefing, and an audit trail. Results: The analysis revealed four major themes describing midwives’ experiences in managing PPH: (1) emotional responses in life-threatening situations, (2) rapid clinical decision-making based on standard operating procedures (SOP) in critical conditions, (3) midwives’ leadership and teamwork within health system limitations, and (4) the integration of spiritual values as a source of strength and professional meaning in clinical practice. Conclusions: Midwives’ experiences in managing postpartum hemorrhage represent a dynamic process involving emotional regulation, adherence to clinical protocols, teamwork, and spiritual coping. The integration of clinical competence and psychosocial support plays an important role in supporting effective clinical decision-making during obstetric emergencies.